A kind of degradable composite polyethylene plastic and preparation method thereof
By adding dopamine-modified microcrystalline cellulose, polyether etherketone/hydroxyapatite composite material and chitosan/nanosilicon dioxide aerogel to the polyethylene plastic, the problems of poor degradability and low mechanical properties of polyethylene plastics are solved, and higher biodegradability and mechanical properties are achieved.
Patent Information
- Application Number
- CN202410188206.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-02-20
AI Technical Summary
The existing polyethylene plastics have poor degradability and low mechanical properties, making it difficult to meet environmentally friendly needs.
The degradability and mechanical properties of the polyethylene are improved by adding components such as dopamine-modified microcrystalline cellulose, polyether ether ketone/hydroxyapatite composites and chitosan/nanosilicon dioxide aerogels.
The biodegradability and mechanical properties of polyethylene plastics are significantly improved, and their degradability and physical properties in the environment are enhanced.
Smart Images

Figure CN118006019B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of plastics, and specifically relates to a degradable composite polyethylene plastic and a preparation method thereof. Background Art
[0002] Plastic has become an indispensable item in people's lives due to its advantages such as high strength, low density and corrosion resistance. However, since plastic products are difficult to degrade, a large amount of solid waste will be generated after use, resulting in its continuous accumulation in the environment, causing a series of soil and water pollution problems.
[0003] Biodegradable plastics refer to a type of degradable plastic that can be decomposed by microorganisms such as bacteria, fungi, algae or enzymes under natural conditions such as soil and sand, or under specific conditions such as composting, anaerobic digestion, and aqueous culture medium, and ultimately completely degraded into carbon dioxide, methane, water, mineralized inorganic salts of the elements it contains, and new biomass. The production process of natural polymer biodegradable plastics is relatively simple, but the products produced often have poor water resistance, poor thermoplasticity, are brittle, and have low mechanical properties. The comprehensive performance is often far behind that of traditional plastics, and product performance needs to be further improved. Summary of the invention
[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a degradable composite polyethylene plastic and a preparation method thereof. In order to solve the problem of poor degradability of polyethylene plastic, the present invention proposes adding dopamine-modified microcrystalline cellulose, polyetheretherketone / hydroxyapatite composite materials and chitosan / nano-silica aerogel into polyethylene to improve the degradability and mechanical properties of polyethylene plastic.
[0005] In order to achieve the above-mentioned purpose, the technical scheme adopted by the present invention is as follows: The present invention proposes a degradable composite polyethylene plastic and a preparation method thereof, wherein the degradable composite polyethylene plastic comprises the following components in parts by weight: 80-100 parts of low-density polyethylene, 8-12 parts of starch, 5-8 parts of dopamine-modified microcrystalline cellulose, 10-15 parts of polyetheretherketone / hydroxyapatite composite material, 15-20 parts of chitosan / nano-silica aerogel, 2-3 parts of polyethylene wax, and 3-5 parts of glycerol.
[0006] Furthermore, the preparation method of the dopamine-modified microcrystalline cellulose is as follows:
[0007] Place microcrystalline cellulose in a beaker, add 100 mL of deionized water, adjust the pH value to 8.5 with hydrochloric acid buffer, add dopamine, stir at 30°C for 3-4 hours, centrifuge to obtain the precipitate, and dry it in a drying oven at 60°C for 10 hours to obtain dopamine-modified microcrystalline cellulose.
[0008] Furthermore, the mass ratio of microcrystalline cellulose to dopamine is 1:0.3-0.4, the centrifugal speed is 3000-4000rpm, and the time is 1-2h.
[0009] Furthermore, the preparation method of the polyetheretherketone / hydroxyapatite composite material is as follows:
[0010] Take hydroxyapatite and polyetheretherketone and add them to anhydrous ethanol, place them in an ultrasonic disperser for ultrasonic dispersion for 1 hour, then filter out the mixture, place it in an oven and dry it at 90°C for 10 hours, and extrude it with a twin-screw extruder to obtain a polyetheretherketone / hydroxyapatite composite material.
[0011] Furthermore, the mass ratio of hydroxyapatite to polyetheretherketone is 1-2:20, the power of ultrasonic dispersion is 300W, the extrusion temperature is 370°C-400°C, and the rotation speed is 60r / min.
[0012] Furthermore, the preparation method of the chitosan / nano-silica aerogel comprises the following steps:
[0013] S1. Add chitosan to 50 mL of 0.2% acetic acid solution, stir magnetically at 500 rpm for 30 min at 50°C to obtain a chitosan solution, add nano-silica to 50 mL of anhydrous ethanol, stir for 30 min to obtain a mixed solution;
[0014] S2. The chitosan solution and the mixed solution obtained in step S1 were transferred to a beaker, magnetically stirred at 500 r / min in a 40°C water bath for 24 h, and then centrifuged at 8000 r / min in a centrifuge to remove the supernatant. The precipitate was washed with ethanol solution and ultrapure water in turn until the supernatant was colorless, and the precipitate was placed in a -20°C refrigerator for 24 h, and freeze-dried to obtain chitosan / nano-silica aerogel.
[0015] Furthermore, in step S1, the mass ratio of chitosan to nano-silicon dioxide is 3:1-2.
[0016] The present invention provides a method for preparing a degradable composite polyethylene plastic, which specifically comprises the following steps:
[0017] Starch, dopamine-modified microcrystalline cellulose, polyetheretherketone / hydroxyapatite composite material, and chitosan / nano-silica aerogel are stirred and mixed evenly, and then polyethylene wax and glycerin are added and continued to be stirred and mixed, and finally low-density polyethylene is added and mixed evenly, and then placed in an internal mixer for internal mixing. After the mixture is mixed, it is cooled and crushed, transferred to a twin-screw extruder, extruded into granules after mixing, and shaped by an injection machine to obtain a degradable composite polyethylene plastic.
[0018] The beneficial effects achieved by the present invention are as follows:
[0019] Microcrystalline cellulose is a hydrolysis product of natural cellulose, with a relatively complete crystalline structure and a large aspect ratio, so it has degradability and excellent mechanical properties. Dopamine can be self-oxidized under alkaline conditions to form polydopamine and coated on the surface of microcrystalline cellulose, improving the compatibility of microcrystalline cellulose with the matrix and the dispersibility in the matrix, thereby improving the mechanical properties of plastics; polyetheretherketone has good chemical stability, water resistance and thermal stability. Hydroxyapatite, as the main inorganic component in natural bone materials, makes bone materials have excellent mechanical properties. Therefore, adding hydroxyapatite to polyetheretherketone as an inorganic filler can improve the mechanical properties of the composite material, and adding it to polyethylene can improve the comprehensive performance of plastics; chitosan has very good degradability, but its own stability is poor. Chitosan and nano-silicon dioxide are composited to prepare aerogels and added to polyethylene, which improves the degradability of plastics while having good stability. In addition, the porous structure of aerogels can provide more adsorption sites for microorganisms, which is more conducive to degradation; polyethylene wax and glycerol effectively reduce the friction between the components, improve the internal flexibility and surface smoothness, and improve the overall mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The tensile properties test results of Examples 1-3 and Comparative Examples 1-3 of the present invention are shown in FIG.
[0021] Figure 2 The bending performance test results of Examples 1-3 and Comparative Examples 1-3 of the present invention are shown in FIG.
[0022] Figure 3 The biodegradability test results of Examples 1-3 and Comparative Examples 1-3 of the present invention are shown in FIG.
[0023] Figure 4 This is a scanning electron microscope image of the degradable composite polyethylene plastic prepared in Example 1 of the present invention.
[0024] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0027] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.
[0028] Example 1
[0029] A degradable composite polyethylene plastic comprises the following components in parts by weight: 80 parts of low-density polyethylene, 8 parts of starch, 5 parts of dopamine-modified microcrystalline cellulose, 10 parts of polyetheretherketone / hydroxyapatite composite material, 15 parts of chitosan / nano-silica aerogel, 2 parts of polyethylene wax and 3 parts of glycerol.
[0030] The preparation method of the dopamine-modified microcrystalline cellulose is as follows:
[0031] Take 1g of microcrystalline cellulose and put it in a beaker, add 100mL of deionized water, use hydrochloric acid buffer to adjust the pH value to 8.5, add 0.3g of dopamine, stir at 30°C for 3h, centrifuge to obtain the precipitate after the end, the centrifugation speed is 3000rpm, the time is 1h, and dry in a drying oven at 60°C for 10h to obtain dopamine-modified microcrystalline cellulose.
[0032] The preparation method of the polyetheretherketone / hydroxyapatite composite material is as follows:
[0033] Take 1g of hydroxyapatite and 20g of polyetheretherketone, add them to anhydrous ethanol, place them in an ultrasonic disperser for ultrasonic dispersion for 1 hour, the ultrasonic dispersion power is 300W, then filter and separate the mixture, place it in an oven at 90°C and dry it for 10 hours, and extrude it with a twin-screw extruder at an extrusion temperature of 370°C and a rotation speed of 60r / min to obtain a polyetheretherketone / hydroxyapatite composite material.
[0034] The preparation method of the chitosan / nano-silicon dioxide aerogel comprises the following steps:
[0035] S1. Take 3 g of chitosan and add it to 50 mL of 0.2% acetic acid solution, stir it with magnetic force at 500 r / min at 50°C for 30 min to obtain a chitosan solution, take 1 g of nano-silica and add it to 50 mL of anhydrous ethanol, stir it for 30 min to obtain a mixed solution;
[0036] S2. The chitosan solution and the mixed solution obtained in step S1 were transferred to a beaker, magnetically stirred at 500 r / min in a 40°C water bath for 24 h, and then centrifuged at 8000 r / min in a centrifuge to remove the supernatant. The precipitate was washed with ethanol solution and ultrapure water in turn until the supernatant was colorless, and the precipitate was placed in a -20°C refrigerator for 24 h, and freeze-dried to obtain chitosan / nano-silica aerogel.
[0037] This embodiment provides a method for preparing a degradable composite polyethylene plastic, which specifically comprises the following steps:
[0038] Starch, dopamine-modified microcrystalline cellulose, polyetheretherketone / hydroxyapatite composite material, and chitosan / nano-silica aerogel are stirred and mixed evenly, and then polyethylene wax and glycerin are added and continued to be stirred and mixed, and finally low-density polyethylene is added and mixed evenly, and then placed in an internal mixer for internal mixing. After the mixture is mixed, it is cooled and crushed, transferred to a twin-screw extruder, extruded into granules after mixing, and shaped by an injection machine to obtain a degradable composite polyethylene plastic.
[0039] Example 2
[0040] A degradable composite polyethylene plastic comprises the following components in parts by weight: 100 parts of low-density polyethylene, 12 parts of starch, 8 parts of dopamine-modified microcrystalline cellulose, 15 parts of polyetheretherketone / hydroxyapatite composite material, 20 parts of chitosan / nano-silica aerogel, 3 parts of polyethylene wax and 5 parts of glycerol.
[0041] The preparation method of the dopamine-modified microcrystalline cellulose is as follows:
[0042] Take 1g of microcrystalline cellulose and put it in a beaker, add 100mL of deionized water, use hydrochloric acid buffer to adjust the pH value to 8.5, add 0.4g of dopamine, stir at 30°C for 4h, centrifuge to obtain the precipitate after the end, the centrifugation speed is 4000rpm, the time is 2h, and dry in a drying oven at 60°C for 10h to obtain dopamine-modified microcrystalline cellulose.
[0043] The preparation method of the polyetheretherketone / hydroxyapatite composite material is as follows:
[0044] Take 2g of hydroxyapatite and 20g of polyetheretherketone, add them to anhydrous ethanol, place them in an ultrasonic disperser for ultrasonic dispersion for 1 hour, the ultrasonic dispersion power is 300W, then filter and separate the mixture, place it in an oven at 90°C and dry it for 10h, and extrude it with a twin-screw extruder at an extrusion temperature of 400°C and a rotation speed of 60r / min to obtain a polyetheretherketone / hydroxyapatite composite material.
[0045] The preparation method of the chitosan / nano-silicon dioxide aerogel comprises the following steps:
[0046] S1. Take 3 g of chitosan and add it to 50 mL of 0.2% acetic acid solution, stir it with magnetic force at 500 r / min at 50°C for 30 min to obtain a chitosan solution, take 2 g of nano-silica and add it to 50 mL of anhydrous ethanol, stir it for 30 min to obtain a mixed solution;
[0047] S2. The chitosan solution and the mixed solution obtained in step S1 were transferred to a beaker, magnetically stirred at 500 r / min in a 40°C water bath for 24 h, and then centrifuged at 8000 r / min in a centrifuge to remove the supernatant. The precipitate was washed with ethanol solution and ultrapure water in turn until the supernatant was colorless, and the precipitate was placed in a -20°C refrigerator for 24 h, and freeze-dried to obtain chitosan / nano-silica aerogel.
[0048] This embodiment provides a method for preparing a degradable composite polyethylene plastic, and the preparation method is carried out with reference to Example 1.
[0049] Example 3
[0050] A degradable composite polyethylene plastic comprises the following components in parts by weight: 90 parts of low-density polyethylene, 10 parts of starch, 7 parts of dopamine-modified microcrystalline cellulose, 12 parts of polyetheretherketone / hydroxyapatite composite material, 17 parts of chitosan / nano-silicon dioxide aerogel, 2.5 parts of polyethylene wax and 4 parts of glycerol.
[0051] The preparation method of the dopamine-modified microcrystalline cellulose is as follows:
[0052] Take 1g of microcrystalline cellulose and put it in a beaker, add 100mL of deionized water, use hydrochloric acid buffer to adjust the pH value to 8.5, add 0.35g of dopamine, stir at 30°C for 4h, and then centrifuge to obtain the precipitate at a speed of 4000rpm for 2h. Dry it in a drying oven at 60°C for 10h to obtain dopamine-modified microcrystalline cellulose.
[0053] The preparation method of the polyetheretherketone / hydroxyapatite composite material is as follows:
[0054] Take 1.5g of hydroxyapatite and 20g of polyetheretherketone, add them to anhydrous ethanol, place them in an ultrasonic disperser for ultrasonic dispersion for 1 hour, the ultrasonic dispersion power is 300W, then filter and separate the mixture, place it in an oven at 90°C and dry it for 10h, and extrude it with a twin-screw extruder at an extrusion temperature of 380°C and a rotation speed of 60r / min to obtain a polyetheretherketone / hydroxyapatite composite material.
[0055] The preparation method of the chitosan / nano-silicon dioxide aerogel comprises the following steps:
[0056] S1. Take 3 g of chitosan and add it to 50 mL of 0.2% acetic acid solution, stir it with magnetic force at 500 r / min at 50°C for 30 min to obtain a chitosan solution, take 1.5 g of nano-silica and add it to 50 mL of anhydrous ethanol, stir it for 30 min to obtain a mixed solution;
[0057] S2. The chitosan solution and the mixed solution obtained in step S1 were transferred to a beaker, magnetically stirred at 500 r / min in a 40°C water bath for 24 h, and then centrifuged at 8000 r / min in a centrifuge to remove the supernatant. The precipitate was washed with ethanol solution and ultrapure water in turn until the supernatant was colorless, and the precipitate was placed in a -20°C refrigerator for 24 h, and freeze-dried to obtain chitosan / nano-silica aerogel.
[0058] This embodiment provides a method for preparing a degradable composite polyethylene plastic, and the preparation method is carried out with reference to Example 1.
[0059] Comparative Example 1
[0060] This comparative example provides a degradable composite polyethylene plastic and a preparation method thereof, which is different from Example 1 in that dopamine-modified microcrystalline cellulose is not included in all components, and the remaining components and component contents are the same as those in Example 1.
[0061] Comparative Example 2
[0062] This comparative example provides a degradable composite polyethylene plastic and a preparation method thereof, which is different from Example 1 in that all components do not contain polyetheretherketone / hydroxyapatite composite materials, and the remaining components and component contents are the same as those in Example 1.
[0063] Comparative Example 3
[0064] This comparative example provides a degradable composite polyethylene plastic and a preparation method thereof, which is different from Example 1 in that all components do not contain chitosan / nano-silica aerogel, and the remaining components and component contents are the same as those in Example 1.
[0065] Experimental example
[0066] 1. The tensile properties of the degradable composite polyethylene plastics prepared in Examples 1-3 and Comparative Examples 1-3 of the present invention were tested. The specific method was based on GB / T 1040.1-2018. The strip width was 10 mm, the thickness was 4 mm, and the tensile speed was 5 mm / min.
[0067] 2. The bending performance of the degradable composite polyethylene plastics prepared in Examples 1-3 of the present invention and Comparative Examples 1-3 was tested. The specific method was based on GB / T 9341-2008. The width of the strip was 10 mm, the thickness was 4 mm, and the bending speed was 2 mm / min.
[0068] 3. The biodegradability analysis test of the degradable composite polyethylene plastics prepared in Examples 1-3 of the present invention and Comparative Examples 1-3 was carried out, and biodegradation was carried out by landfill degradation. After 60 days, the remaining mass was measured and the degradation rate was calculated.
[0069] Degradation rate = (mass before degradation - remaining mass) / mass before degradation × 100%.
[0070] 4. The surface morphology of the degradable composite polyethylene plastic prepared in Example 1 was observed using a scanning electron microscope.
[0071] Results Analysis
[0072] Figure 1 This is a graph showing the tensile properties test results of Examples 1-3 and Comparative Examples 1-3 of the present invention. As shown in the figure, the tensile strengths of Examples 1-3 are 10.7 MPa, 11.3 MPa, and 10.1 MPa, respectively, and those of Comparative Examples 1-3 are 6.2 MPa, 7.1 MPa, and 8.4 MPa, respectively.
[0073] Figure 2 This is a graph showing the bending performance test results of Examples 1-3 of the present invention and Comparative Examples 1-3. As shown in the figure, the tensile strengths of Examples 1-3 are 7.9 MPa, 8.2 MPa, and 7.6 MPa, respectively, and those of Comparative Examples 1-3 are 5.7 MPa, 5.8 MPa, and 6.1 MPa, respectively.
[0074] Figure 3 This is a graph showing the biodegradability test results of Examples 1-3 and Comparative Examples 1-3 of the present invention. As shown in the figure, the degradation rates of Examples 1-3 are 56.2%, 57.1%, and 56.8%, respectively, and those of Comparative Examples 1-3 are 38.2%, 41.1%, and 34.7%, respectively.
[0075] comprehensive Figure 1 , Figure 2 and Figure 3 It can be seen that the addition of dopamine-modified microcrystalline cellulose, polyetheretherketone / hydroxyapatite composites, and chitosan / nanosilica aerogel can significantly improve the mechanical properties and degradability of polyethylene plastics.
[0076] Figure 4 This is a scanning electron microscope image of the degradable composite polyethylene plastic prepared in Example 1 of the present invention.
[0077] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.
[0078] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A degradable composite polyethylene plastic, characterized in that: The degradable composite polyethylene plastic comprises the following components in parts by weight: 80-100 parts of low-density polyethylene, 8-12 parts of starch, 5-8 parts of dopamine-modified microcrystalline cellulose, 10-15 parts of polyetheretherketone / hydroxyapatite composite material, 15-20 parts of chitosan / nano-silicon dioxide aerogel, 2-3 parts of polyethylene wax, and 3-5 parts of glycerol; The specific steps of preparing the polyetheretherketone / hydroxyapatite composite material include: Hydroxyapatite and polyetheretherketone are added to anhydrous ethanol, placed in an ultrasonic disperser for ultrasonic dispersion for 1 hour, then the mixture is separated by filtration, placed in an oven for drying at 90° C. for 10 hours, and mixed and extruded by a twin-screw extruder to obtain a polyetheretherketone / hydroxyapatite composite material; The mass ratio of the hydroxyapatite to polyetheretherketone is 1-2:
20.
2. The degradable composite polyethylene plastic according to claim 1, characterized in that: The specific steps of preparing the dopamine-modified microcrystalline cellulose include: Place microcrystalline cellulose in a beaker, add 100 mL of deionized water, adjust the pH value to 8.5 with hydrochloric acid buffer, add dopamine, stir at 30°C for 3-4 hours, centrifuge to obtain the precipitate, and dry it in a drying oven at 60°C for 10 hours to obtain dopamine-modified microcrystalline cellulose.
3. A degradable composite polyethylene plastic according to claim 2, characterized in that: The mass ratio of microcrystalline cellulose to dopamine is 1:0.3-0.4; the centrifugal speed is 3000-4000rpm, and the centrifugal time is 1-2h.
4. The degradable composite polyethylene plastic according to claim 1, characterized in that: The power of ultrasonic dispersion is 300W; the extrusion temperature is 370℃-400℃, and the rotation speed is 60r / min.
5. The degradable composite polyethylene plastic according to claim 1, characterized in that: The preparation method of the chitosan / nano-silicon dioxide aerogel comprises the following steps: S1, add chitosan to 50 mL of 0.2 wt% acetic acid solution, stir magnetically at 500 r / min at 50°C for 30 min to obtain a chitosan solution, add nano-silica to 50 mL of anhydrous ethanol, stir for 30 min to obtain a mixed solution; S2. The chitosan solution and the mixed solution obtained in step S1 were transferred to a beaker, magnetically stirred at 500 r / min in a 40°C water bath for 24 h, and then centrifuged at 8000 r / min in a centrifuge to remove the supernatant. The precipitate was washed with ethanol solution and ultrapure water in turn until the supernatant was colorless, and the precipitate was placed in a -20°C refrigerator for 24 h, and freeze-dried to obtain chitosan / nano-silica aerogel.
6. The degradable composite polyethylene plastic according to claim 5, characterized in that: In step S1, the mass ratio of chitosan to nano-silicon dioxide is 3:1-2.
7. A method for preparing a degradable composite polyethylene plastic according to any one of claims 1 to 6, characterized in that: The specific steps include: Starch, dopamine-modified microcrystalline cellulose, polyetheretherketone / hydroxyapatite composite material, and chitosan / nano-silica aerogel are stirred and mixed evenly, and then polyethylene wax and glycerin are added and continued to be stirred and mixed, and finally low-density polyethylene is added and mixed evenly, and then placed in an internal mixer for internal mixing. After the mixture is mixed, it is cooled and crushed, transferred to a twin-screw extruder, extruded into granules after mixing, and shaped by an injection machine to obtain a degradable composite polyethylene plastic.
Citation Information
Patent Citations
Preparation method of nano SiO2-chitosan 3D gel and application of gel in cigarette filter tip
CN107556516A
Polyether-ether-ketone / nano-hydroxyapatite composite material and preparation method and application thereof
CN110152068A